The Influence of Farmers Characteristics on Community Interest in Cattle Farming: A Quantitative Study in Taji Village, Jabung District, Malang Regency - Abdaniel Aulasamai Akhzdor; Anie Eka Kusumastuti (CV. Komunitas Dunia Peternakan, 2026)
Cattle farming plays a strategic role in rural economic development by generating employment, supplementary household income, and contributing to food and nutritional security. However, in Indonesia, most smallholder cattle enterprises remain traditional and small-scale, leading farmers to treat livestock farming primarily as a secondary livelihood. While previous studies have largely focused on technical adoption and production performance, limited attention has been given to farmers’ psychological interest as a foundation for sustaining livestock enterprises. Therefore, this study aims to analyze the level of community interest in cattle farming and examine the influence of farmers’ characteristics (age, education level, herd size, number of family dependents, farming experience, and primary income) on such interest. A quantitative survey was conducted involving 34 cattle farmers in Taji Village, Jabung District, Malang Regency, selected using total sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings reveal that community interest in cattle farming is generally high, as reflected in emotional (3.93), cognitive (3.81), and conative (3.74) dimensions measured on a four-point Likert scale. Regression results indicate that age has a significant positive effect (p = 0.022), whereas farming experience has a significant negative effect (p = 0.025) on interest levels. Other variables show no statistically significant influence. These findings highlight that psychological engagement in cattle farming is shaped more by demographic and experiential factors than by formal education or income level. The study contributes to the literature by positioning interest as a psychological determinant of livestock sustainability. Policy implications emphasize the urgency of risk-mitigation extension programs to address farmer burnout, incentivized intergenerational knowledge transfer, and cooperative-based institutional support to ensure smallholder livestock sustainability.